Cognitive aging in rural communities: preliminary memory characterization of a community cohort from Southern Nevada - Miller, Justin B.; Wong, Christina G.; Caldwell, Jessica Z. K.; Rodrigues, Jessica; Pudumjee, Shehroo; John, Samantha E.; Ritter, Aaron (Frontiers in Dementia, 2023)
Rural-dwelling older adults face unique health challenges that may increase risk for Alzheimer's disease and dementia but are underrepresented in aging research. Here, we present an initial characterization of a rural community cohort compared to an urban cohort from the same region. Adults over age 50 living in a non-metropolitan area are clinically characterized using the Uniform Data Set, enriched with additional measures of verbal and nonverbal memory measures. Neighborhood disadvantage is also assessed. Clinical and cognitive differences between cohorts were explored after stratifying by cognitive impairment.Between group comparisons found that rural-dwellers demonstrated better verbal memory than urban-dwellers on primary indices of learning, recall, and recognition, with small to medium effects in overall comparisons. When stratified by impairment, rural-urban differences were notably larger among cognitively normal individuals. Within-group comparisons found that the magnitude of impairment between cognitively normal and impaired groups was greater among rural dwellers compared to urban-dwellers. No differences in nonverbal memory or overall clinical status were found, and there were no effects of neighborhood disadvantage on any cognitive measure. DISCUSSION: Living in a rural community presents a complex set of contextual factors that for some, may increase risk for dementia. In this study, we found small to moderate memory advantages for rural-dwellers, leaving open the possibility that late-life rural living may be advantageous for some and promote resilience. Additional prospective research is critically needed to better understand the factors that influence aging outcomes in this underrepresented population.